Development of a clinical decision support system for living kidney donor assessment based on national guidelines - Knight, SR; Cao, K; South, M; Hunter, J; Hayward, N; Fox, J (Lippincott, Williams and Wilkins, 2018)
Background: Live donor nephrectomy is an operation that places the donor at risk of complications without the possibility of medical benefit. Rigorous donor selection and assessment is therefore essential to ensure minimisation of risk and for this reason robust national guidelines exist. Previous studies have demonstrated poor adherence to donor guidelines. Methods: We developed a clinical decision support system (CDSS), based upon national living donor guidelines, to facilitate the identification of contraindications, additional investigations, special considerations and the decision as to nephrectomy side in potential living donors. The CDSS was then tested with patient data from 45 potential kidney donors. Results: The CDSS comprises 17 core tasks completed by either patient or nurse, and 17 optional tasks that are triggered by certain patient demographics or conditions. Decision rules were able to identify contraindications, additional investigations, special considerations and predicted operation side in our patient cohort. 17/45 patients went on to donate a kidney, of whom 7 had major contraindications defined in the national guidelines, many of which were not identified by the clinical team. Only 43% of additional investigations recommended by national guidelines were completed, with the most frequently missed investigations being oral glucose tolerance testing and routine cancer screening. Conclusions: We have demonstrated the feasibility of turning a complex set of national guidelines into an easy-to-use machine-readable CDSS. Comparison with real-world decisions suggests that use of this CDSS may improve compliance with guidelines and informed consent tailored to individual patient risks.